Sustainable Business Training for MSMEs in Surakarta: Introduction to ESG, Fraud Prevention, and Strengthening Governance through Diversity - Setiawati, Erma; Siti Aisyah Salim; Shinta Permata Sari; Eskasari Putri; Chania Aulia; Roostina Nugraheni Putri (Universitas Muhammadiyah Surakarta, 2025)
The advancement of technology and globalization has significantly changed production methods and environmental conditions, bringing economic benefits while also creating challenges such as pollution and climate change. Therefore, MSMEs in Indonesia need to adopt more responsible and sustainable business practices by applying Environmental, Social, and Governance (ESG) principles, fraud prevention, and strengthened governance supported by diversity. This study discusses an ESG training program conducted by the community service team of Universitas Muhammadiyah Surakarta to help MSMEs understand ESG, prevent fraud, and build stronger governance within their organizations. The results show that although challenges still exist in implementing ESG and good governance, the training successfully improved the participants’ knowledge and capabilities, enabling MSMEs to compete more effectively in the modern business environment while contributing to environmental and social sustainability.